Drug interaction study of natural steroids from herbs specifically toward human UDP-glucuronosyltransferase (UGT) 1A4 and their quantitative structure activity relationship (QSAR) analysis for prediction. (August 2016) - Xu, Min; Dong, Peipei; Tian, Xiangge; Wang, Chao; Huo, Xiaokui; Zhang, Baojing; Wu, Lijun; Deng, Sa; Ma, Xiaochi
Graphical abstract: Abstract: The wide application of herbal medicines and foods containing steroids has resulted in the high risk of herb-drug interactions (HDIs). The present study aims to evaluate the inhibition potential of 43 natural steroids from herb medicines toward human UDP- glucuronosyltransferases (UGTs). A remarkable structure-dependent inhibition toward UGT1A4 was observed in vitro . Some natural steroids such as gitogenin, tigogenin, and solasodine were found to be the novel selective inhibitors of UGT1A4, and did not inhibit the activities of major human CYP isoforms. To clarify the possibility of the in vivo interaction of common steroids and clinical drugs, the kinetic inhibition type and related kinetic parameters (Ki ) were measured. The target compounds 2–6 and 15, competitively inhibited the UGT1A4-catalyzed trifluoperazine glucuronidation reaction, with Ki values of 0.6, 0.18, 1.1, 0.7, 0.8, and 12.3 μM, respectively. And this inhibition of steroids towards UGT1A4 was also verified in human primary hepatocytes. Furthermore, a quantitative structure-activity relationship (QSAR) of steroids with inhibitory effects toward human UGT1A4 isoform was established using the computational methods. Our findings elucidate the potential for in vivo HDI effects of steroids in herbal medicine and foods, with the clinical dr ugs eliminated by UGT1A4, and reveal the vital pharamcophoric requirement of natural steroids for UGT1A4 inhibition activity.